On Pseudohyperbolical Smarandache Curves in Minkowski 3-Space - Esra Betul Koc Ozturk; Ufuk Ozturk; Kazim İlarslan; Emilija Nešović (International Journal of Mathematics and Mathematical Sciences)
We define pseudohyperbolical Smarandache curves according to the Sabban frame in Minkowski 3-space. We obtain the geodesic curvatures and the expression for the Sabban frame vectors of special pseudohyperbolic Smarandache curves. Finally, we give some examples of such curves.